The state of radiology subspecialty training in the west African subregion: the residents' perspective (2013)
Background/Aim: Radiology residency was initiated nearly 30 years ago in the west African subregion, but accompanying formal subspecialty training has been developed within the 30 year time span. In contrast, subspecialization has evolved over the past 25 years in developed countries. The aim of this study was to determine residents' perspective about radiology subspecialization training in west africa. Materials and Methods: Semi- structured, self- administered electronic questionnaire were sent to residents at different levels of training via-email and during update courses. Data analysis was performed using SPSS version 15.0(BM) package. Quantitative variables were expressed using summary statistics including means and medians. Descriptive analysis was performed for the qualitative variables using frequencies, proportions and charts. Statistical significancwe was set at the 5% level using two tailed P values. Results: There were 117 respondents 85(72.6%) males and 32(27.4%) females. A total of 110 (94%) were aware of the various subspecialties in radiology with neuroradiology being identified by all as seperate subspecialty. Interventional radiology topped the choice of subspecialty with 61(52.1%) respondents, and 67(57.3%) would prefer that subspecialties be introduced in phases. Ultrasound, basic x-ray, momography equipment, and computed tomography scanners are availabe in many of the training centers. 116(99.1%) of the resident believed that there is a need for subspecialization in the subregion. Conclusion: Our study demonstrates the need for subspecialzation in west Africa. To achieve this goal, collaboration and support from well-established radiology residency and fellowship training programs based in developed countries is necessary.